2019
DOI: 10.3390/plants8110511
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Enantiomeric Distribution, and Sensory Evaluation of the Essential Oils Distilled from the Ecuadorian Species Myrcianthes myrsinoides (Kunth) Grifo and Myrcia mollis (Kunth) DC. (Myrtaceae)

Abstract: The essential oils of Myrcianthes myrsinoides and Myrcia mollis, belonging to the Myrtaceae family, were obtained by steam distillation. They were analyzed by gas chromatography-mass spectrometry (GC-MS), gas chromatography-flame ionization detector (GC-FID), enantioselective gas chromatography, and gas chromatography-olfactometry (GC-O). A total of 58 compounds for Myrcianthes myrsinoides essential oil (EO) and 22 compounds for Myrcia mollis EO were identified and quantified by GC-MS with apolar and polar col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…All the methods recorded that 1,8-cineole was one of the compounds highest in antioxidant capacity. This finding was similar to several other types of research, which suggested the efficacy of 1,8-cineole as the dominant anticholinesterase agent from EOs of different sources [ 8 , 21 , 25 , 152 ].…”
Section: Discussionsupporting
confidence: 91%
“…All the methods recorded that 1,8-cineole was one of the compounds highest in antioxidant capacity. This finding was similar to several other types of research, which suggested the efficacy of 1,8-cineole as the dominant anticholinesterase agent from EOs of different sources [ 8 , 21 , 25 , 152 ].…”
Section: Discussionsupporting
confidence: 91%
“…Specimens A and B of E. punicifolia had 0.26% and 0.14%, of EOs, respectively, while specimens A and B of M. tomentosa had EO contents of 0.35%, and 0.41%, respectively. These findings corroborate with those of several previous studies, which have suggested that the yields of EOs from different Myrtaceae species vary according to the studied species and the season of collection [20][21][22][23][24].…”
Section: Yields Of Essential Oilssupporting
confidence: 92%
“…Among the natural products the authors are interested in, we can cite essential oils (EOs) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. According to the European Pharmacopeia, an EO is an “odorous product, usually of complex composition, obtained from a botanically defined plant raw material by steam distillation, dry distillation, or a suitable mechanical process without heating.…”
Section: Introductionmentioning
confidence: 99%